Comparative Analysis of Depression, Anxiety, and Stress Scores among Nurses in Different Departments from a Single Center in North India - Bansal, Manishi; Jindal, Ankush; Walia, Rashika; Jindal, Anupam; Gupta, Rimple (International Journal of Nursing Research, 2023)
Introduction: Mental health of health care workers is of utmost importance as they are at high risk of psychological problems due to the demanding nature of their profession. Periodic assessment of nurse’s mental health should be of priority so that timely measures can be taken. Aims and Objectives: This study was conducted with the aim to assess – (1) the prevalence of depression, anxiety, and stress among intensive care unit (ICU), operation theater (OT), and inpatient ward (IPD) nurses, (2) to compare the levels of depression, anxiety, and stress within departments, and (3) to correlate the level of above parameters with certain variables. Materials and Methods: A cross-sectional study was conducted at Mayo Super Specialty Hospital, India. A total of 90 nursing staffs were interviewed regarding incidence of depression, anxiety, and stress using a DASS pro forma. The scores were then interpreted according to the categories given in the pro forma. Results: Out of the 90 study participants, 30 were male and 60 were female. Average age was 29 years. The overall prevalence of depression in ICU, OT, and IPD was 53.3%, 33.3%, and 40%, respectively. The incidence of anxiety was 73.3% and stress was 40% in ICU which was higher than OT and IPD areas. However, the above differences were not statistically significant. Conclusion: Our study demonstrates that levels of depression, anxiety, and stress were higher among nursing staff of ICU as compared to other areas within the same hospital and timely preventive measures should be taken to avoid any serious mental illness.